مدى تطبيق قواعد الحوكمة في الشركات العراقية: دراسة تحليلية وتطبيقية على الشركات العامة العراقية - علاوي، خضير مجيد (جامعة القادسية - كلية الادارة والاقتصاد, 2015)
تعد الحاكمية المؤسسية ضرورة فرضتها الحياة على الشركات، خصوصا فى ظل الظروف التي نشأ بها تعارض مصالح الأطراف الفاعلين في العمليات الاقتصادية، سواء كانوا مستثمرين أو عاملين أومديرين في تلك الشركات، والغاية من تبني هذا المفهوم محاربة الفساد المالي والاداري، وتقليل حالة التعارض بين الاطراف المتعاملة مع الوحدات الاقتصادية ، وان من أهم الدعائم الهامة التي تبنى عليها الحاكمية المؤسسية هي الشفافية ومصداقية التقارير المالية المنشورة من طرف الشركات ، ومن هنا يبرز دور الحاكمية المؤسسية التى تعمل على زيادة مصداقية التقارير عن طريق اجراء عملية تدقيق بجودة عالية من أجل تقديم المعلومة المناسبة ورفع درجة موثوقيتها ، وجاءت هذه الدراسة لمعرفة الدور المهم للحاكمية المؤسسية ومدى تطبيقها في الشركات العراقية . من خلال دراسة تحليلية وتطبيقية على احدى الشركات العراقية.
The Corporate Governance necessity imposed by the life companies, especially in light of the circumstances that arose out opposed to the interests of the parties to the actors in the economic processes, whether they are investors or workers or managers in these companies, and the purpose of the adoption of this concept to fight financial and administrative corruption, and reduce the case of conflict between the parties dealing with economic units, and that of the most important pillars of the important upon which to build corporate governance is transparency and credibility financial reports published by companies, and here highlights the role of corporate governance, which works to increase the credibility of the reports by conducting an audit of high quality in order to provide information appropriate to raise the degree of reliability, and this study was to find out the important role of governance and institutional. Through an applied analytical study in one of Iraqi companies
Keywords: العراق -- حوكمة الشركات -- الحوكمة -- الشركات العامة العراقية